PENGARUH LATIHAN HEXAGON DRILL TERHADAP KELINCAHAN TIM BULUTANGKIS SMP ISLAM PLUS JANNATUL FIRDAUS KOTA PEKANBARU - Ridho Mulyo; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problems in this research are footsteps by athletes who still receive long balls, athletes can receive balls well but have not scored opponents giving short balls athletes have difficulty in picking up the ball which causes fast movements in the return to the ready or center of the field. While the purpose of this study was to study the existence of a simulated hexagon drill exercise on agility in the badminton game of the Islamic Middle School Plus Jannatul Firdaus team. This research was conducted in June 2019 until July 2019 in the JL. Pembina 3 No.109 Limbungan, Rumbai Pesisir, Pekanbaru City. This type of research is an experimental study (experimental), the participants of this study were the Jannatul Firdaus Islamic Middle School team, the sample in this study were all study participants who examined 8 people. Data collection techniques can be from pree-test and post-test. The instrument used in this study was theshuttle run, before analysis was carried out, before the pre-test was done with an average of 16.57. Then the hexagon drill exercise was conducted for 16 meetings on the Islamic Middle School Plus Jannatul Firdaus team that helped 8 people and obtained an average post-test score of 16.34. Based on the analysis of pree-test and post-test data there are differences in numbers that increase or increase by 0.23. Means tcount> ttable. Based on the results of the analysis, it can be concluded as follows: related to hexagon drill (X) training on agility (Y) on the extracurricular team at the Islamic Middle School Plus Jannatul Firdaus.Key Words: Hexagon Drill Exercise, Agility